Optimization of the Development and Market Share Growth of Sharia Insurance in the Modern Era - Yusri, Muhammad; Sholatiah, Sholatiah; Fadholina, Cania Ainusifa; Hidayati, Tri (Universitas Siliwangi, 2025)
Introduction to The Problem: The Islamic insurance industry in Indonesia has great potential to grow, especially considering the majority of Indonesia's population is Muslim. However, in reality, the market share of Islamic insurance in Indonesia is still lagging behind compared to other financial institutions and when compared to conventional insurance. Based on data as of December 31, 2022, it shows that conventional insurance premiums have a market share of 50.32%, social and compulsory insurance premiums are 45%, while Islamic insurance premiums only reach 4.76%.Purpose/Objective Study: This study aims to analyze strategies to optimize the development and increase market share of Islamic insurance in the modern era.Design/Methodology/Approach: This research uses a qualitative method with a descriptive approach to review literature related to marketing strategies, technological innovation, consumer behavior, and regulations in Islamic insurance.Findings: The research findings show that optimization of development can be achieved through product innovation in accordance with modern market needs, the application of digital technology, and increased Islamic financial literacy.In addition, strong regulatory support from the government, both from DSN-MUI and OJK, is essential in creating a conducive environment for the growth of Islamic insurance.The conclusion of this study states that collaborative strategies between Islamic insurance companies and related industries, as well as the utilization of digital technology, can increase the market share and competitiveness of Islamic insurance in the modern era.This optimization can expand product range and increase consumer confidence, as well as strengthen the position of Islamic insurance in the global financial market.Paper Type: Research Article